2018
DOI: 10.3390/ma11061047
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Preparation of Plasma-Modified Fly Ash Catalyst and Its De–NOX Mechanism

Abstract: Fly ash and bentonite were mixed in a certain proportion as raw materials to prepare a denitration catalyst. In previous studies, it has been concluded that fly ash-type catalysts can provide significant catalytic activity for denitrification after being modified with oxygen. In this study, the effect of plasma conditions on the denitration performance of the catalyst was investigated from the aspects of plasma modification power, modification time, and the flow rate of the gas. Boehm titration and infrared an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…By modification, fly ash can form a pore structure and rougher surface, greatly increasing its specific surface area and effectively enhancing its performance in adsorption, catalysis, and other aspects. The common modification methods include acid modification, alkali modification, and plasma modification [43][44][45].…”
Section: Direct Modificationmentioning
confidence: 99%
“…By modification, fly ash can form a pore structure and rougher surface, greatly increasing its specific surface area and effectively enhancing its performance in adsorption, catalysis, and other aspects. The common modification methods include acid modification, alkali modification, and plasma modification [43][44][45].…”
Section: Direct Modificationmentioning
confidence: 99%
“…It was observed that the concentrations of O atoms, Mn 4+ and Co 2+ on the surface of Mn-CoO x were significantly increased after plasma treatment, which were the key to NO oxidation. Zhang et al [114] proposed that the discharge power, treatment time, and airflow of O 2 gas during plasma treatment would increase the basic functional groups, thereby improving the denitration activity. It was revealed that the removal efficiency of NO of plasma-modified catalyst reaches 95% within 1 min under the conditions of 60 W power, a treatment time of 20 min, and an air flow of 40 ml/min.…”
Section: Denitrationmentioning
confidence: 99%
“…Bentonite can absorb 5 times its own weight in water because the unit cell particles are not large and the surface is broad, irregular, and charged. Expansive soil is evenly mixed with fly ash and aqueous solution and then blended together. During the extrusion molding process, the stability of the extruded catalyst is greatly ensured, and the change of the catalyst form is prevented . So far, proven cumulative reserves have exceeded 5.087 billion tons, and the unreserved reserves are expected to exceed 7 billion tons.…”
Section: Introductionmentioning
confidence: 99%